Higher Dietary Inflammatory Index Scores are Associated with Increased Odds of Benign Breast Diseases in a Case–Control Study - Aghababayan S (Dove Medical Press, 2020)
Sama Aghababayan, 1 Zahra Sheikhi Mobarakeh, 2 Mostafa Qorbani, 3, 4 Zeinab Tiznobeyk, 1 Azadeh Aminianfar, 1 Gity Sotoudeh 1 1Department of Community Nutrition, School of Nutritional Sciences and Dietetics, Tehran University of Medical Sciences, Tehran, Iran; 2Department of Cancer Quality of Life, Breast Cancer Research Center, Academic Center for Education, Culture and Research (ACECR), Tehran, Iran; 3Non-Communicable Diseases Research Center, Alborz University of Medical Sciences, Karaj, Iran; 4Chronic Diseases Research Center, Endocrinology and Metabolism Population Sciences Institute, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Gity SotoudehDepartment of Community Nutrition, School of Nutritional Sciences and Dietetics, Tehran University of Medical Sciences, Hojatdost Street, Tehran, IranTel +989123906617Fax +98-21-88974462Email gsotodeh@tums.ac.irZahra Sheikhi MobarakehDepartment of Cancer Quality of Life, Breast Cancer Research Center, Academic Center for Education, Culture and Research (ACECR), 146, South Gandi Avenue, Vanak Square, Tehran 1517964311, IranTel +989128100332Email dr.shaikhi88@gmail.comPurpose: Dietary inflammatory index (DII) is a new tool for assessing the inflammatory potential of diet. Since there is no study that has investigated the association of DII and benign breast diseases (BBD), the aim of our study was to compare DII scores in patients with and without BBD.Methods: One hundred and eleven (111) subjects with BBD and 104 healthy women attending the Iranian Center for Breast Cancer affiliated with the Academic Center for Education, Culture and Research were enrolled in a case–control study. Dietary data collected using a 168‑item validated food frequency questionnaire (FFQ). Energy-adjusted DII was calculated based on FFQ. Socio demographic data were collected by interview. In addition, physical activity was measured by the International Physical Activity Questionnaire (IPAQ). Weight, height and waist circumference were also measured.Results: After adjustment for multiple confounding variables, participants at the highest tertile of DII had increased OR for BBD (OR=1.7, 95% CI=0.75– 3.95) (P-trend =0.04).Conclusion: The increased chance of BBD was suggested with a higher consumption of diets with inflammatory potential. However, this result should be interpreted with caution as OR was not statistically significant. Interventional studies are warranted to elucidate the role of inflammatory diets in the development of BBD.Keywords: benign breast disease, breast cancer, diet, dietary inflammatory index, inflammation